The Legal Awareness of Cafe Owners towards The Fulfillment of Economic Rights in The Form of Royalty Payment as A Copyright Protection: Kesadaran Hukum Pemilik Kafe Terhadap Pemenuhan Hak Ekonomi Berupa Pembayaran Royalti Sebagai Bentuk Perlindungan Hak Cipta - Faisal, Muhammad Hafidz (Annual Review of Legal Studies, 2024)
With the existence of Government Regulation Number 56 of 2021 concerning the Management of Royalties for Copyrighted Songs and/or Music, the commercial use of songs/music is required to pay royalties. Article 2 paragraph (1) and Article 3 paragraphs (1) and (2) of the Government Regulation mention that the party paying royalties through LMKN (Collecting Society for Music Works) is those who publicly announce creations, including cafes that frequently play songs or music through speakers. This research aims to discover facts in the field regarding legal awareness among cafe business operators regarding the payment of these royalties through data triangulation, which involves collecting data through observation, interviews, and documentation. The research location will be initially observed to identify cafes that play songs or music through speakers. After identifying the cafes that play songs or music through speakers, interviews will be conducted with cafe operators to explore their legal awareness regarding copyright and royalty payment obligations, while the researcher gathers documentation as evidence. The findings in the field prove that legal awareness regarding royalty payments is still lacking among many. This is because they have not heard about the royalty policy and also due to a lack of awareness campaigns from the relevant authorities, necessitating awareness campaigns in various regions, as this can be considered a legal violation. Therefore, it can be said that the most influential factor affecting legal awareness here is the legal framework, which should be more proactive in disseminating information regarding this policy and also more stringent in handling violations.